2019
DOI: 10.3390/molecules24132510
|View full text |Cite
|
Sign up to set email alerts
|

The 3S Enantiomer Drives Enolase Inhibitory Activity in SF2312 and Its Analogues

Abstract: We recently reported that SF2312 ((1,5-dihydroxy-2-oxopyrrolidin-3-yl)phosphonic acid), a phosphonate antibiotic with a previously unknown mode of action, is a potent inhibitor of the glycolytic enzyme, Enolase. SF2312 can only be synthesized as a racemic-diastereomeric mixture. However, co-crystal structures with Enolase 2 (ENO2) have consistently shown that only the (3S,5S)-enantiomer binds to the active site. The acidity of the alpha proton at C-3, which deprotonates under mildly alkaline conditions, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…While SF2312 exists as a racemic mixture in solution due to stereocenters at the 3- and 5-positions, it is noteworthy that in our complex structure with E. coli enolase, only the 3 S,5 S configuration is observed. This is further confirmed in the recent work which describes the human ENO2 enolase in complex with the active S,S-enantiomer form of SF2312 14 .…”
Section: Resultssupporting
confidence: 77%
“…While SF2312 exists as a racemic mixture in solution due to stereocenters at the 3- and 5-positions, it is noteworthy that in our complex structure with E. coli enolase, only the 3 S,5 S configuration is observed. This is further confirmed in the recent work which describes the human ENO2 enolase in complex with the active S,S-enantiomer form of SF2312 14 .…”
Section: Resultssupporting
confidence: 77%
“…ENO1 is the major isoform of enolase in cancer cells, accounting for 75–90% of the cellular enolase activity [ 29 ]. In a series of studies by Muller, ENO2-specific inhibitors did not significantly affect enolase activity in ENO1 wild-type cells [ 38 , 39 ]. All the above information suggests that ENO2 promotes CRC metastasis through non-glycolytic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Human ENO1 and ENO2 share 84% sequence identitybearing even higher resemblance in the active site. , Maximizing inhibitor specificity for ENO2 was an important design goal to avoid inhibition of erythrocytic ENO1 the sole isoform present in erythrocyteswhich can result in anemia. , With these constraints, we identified a cyclic derivative of PhAH, deoxySF2312 ( 2 ), which bore close resemblance to the natural product antibiotic, SF2312 ( 3 ; PDB: 4ZCW). We clarified the stereochemical requirements for active site binding by SF2312 by synthesizing a Cα-methyl derivative of SF2312 (mSF2312, 4 ; PDB: 5EU9), which showed that ENO2 binding was specific to the 3 S , 5 S enantiomer . Further structure–activity relationship (SAR) studies aimed at improving ENO2 specificity led to the identification of 1-hydroxy-2-oxopiperidin-3-yl phosphonate (HEX, 5 ; Figure , PDB: 5IDZ).…”
Section: Introductionmentioning
confidence: 99%
“… 8 We clarified the stereochemical requirements for active site binding by SF2312 by synthesizing a Cα-methyl derivative of SF2312 (mSF2312, 4 ; PDB: 5EU9 ), which showed that ENO2 binding was specific to the 3 S , 5 S enantiomer. 14 Further structure–activity relationship (SAR) studies aimed at improving ENO2 specificity led to the identification of 1-hydroxy-2-oxopiperidin-3-yl phosphonate (HEX, 5 ; Figure 1 , PDB: 5IDZ ). 12 Of these four candidates ( Figure 1 c), we focused on the development of 5 due to its clear preference for ENO2 at lower concentrations and lower molecular complexity, which eases the synthesis of prodrug derivatives ( Figure 1 d).…”
Section: Introductionmentioning
confidence: 99%